Analysis of global, regional, and national burdens of neonatal encephalopathy from 1990 to 2021: insights from the Global Burden of Disease Study 2021 - Tan, Shujun; Mageziyi, Shala; Long, Li; Dilimulati, Naiyiman; Hui, Zhang; Rejiafu, Nuerya (Frontiers in Public Health, 2025)
BackgroundThe Sustainable Development Goal 3.2 urges nations to reduce neonatal mortality rates to no more than 12 deaths per 1,000 live births by 2030. Neonatal encephalopathy (NE), the third leading cause of under-five mortality, significantly impacts global neonatal death rates and long-term health. A comprehensive assessment is essential to inform public health strategies. This study aims to analyze the burden of Neonatal Encephalopathy on global, regional, and national levels.MethodsData on the age-standardized mortality rate (ASMR) and age-standardized incidence rates (ASIR) for NE from 1990 to 2021 were obtained from the Global Burden of Disease Study (GBD) 2021. To evaluate the changes in ASIR and ASMR associated with the burden of NE, estimated annual percentage changes (EAPC) and overall percentage changes were calculated. Furthermore, the relationship between disease burden and the Sociodemographic Index (SDI) was analyzed, along with predictions generated using autoregressive integrated moving average (ARIMA) model.ResultsThe global burden of NE has significantly declined over the past three decades. Between 1990 and 2021, the global ASIR decreased from 20.22 to 17.16, while the number of cases fell from 1,295,891.1 to 1,061,448.15, reflecting an 18.09% reduction. Similarly, the global ASMR declined from 13.81 in 1990 to 9.75 in 2021, with deaths decreasing from 883,082.06 to 603,605.62, representing a 31.65% reduction. Projections based on ARIMA models indicate that from 2022 to 2030, the global ASIR is expected to decline from 17.06 to 16.36, and the ASMR is projected to decrease from 9.55 to 7.98, suggesting a continued reduction in the burden of NE.ConclusionThis study illustrates the global progress made in reducing neonatal encephalopathy from 1990 to 2021; however, significant disparities persist. Targeted interventions are crucial to address these inequities and to achieve Sustainable Development Goal 3.2.